Electrochemical performance of LiFePO4/graphene composites at low temperature affected by preparation technology. (1st February 2021) - Zhang, Baofeng; Xu, Youlong; Wang, Jie; Ma, Xiaoning; Hou, Wenqiang; Xue, Xu
Highlights: Stirring and dropping is the best way to prepare LiFePO4 /graphene nanocomposite. It facilitates interplanar spacing, less Fe-Li defects and higher conductivity. Rct, DLi, capacity and activation energy at 2.5 - 4.3 V from −30 - 50 °C are tested. Lithium ion diffusion is the rate-determining step. Simulation reveals that uneven Li + distribution occurs at low temperature. Abstract: Many strategies have been employed to enhance the electrical conductivity and lithium ion diffusion of LiFePO4 under hydrothermal method. But the modification of the crystal structure affected by preparation technology as well as the influence of the modification on the electrochemical performance at low temperature are not fully understood. This paper systematically reports the LiFePO4 /graphene nanocomposites synthesized with different preparing techniques. Among the four methods employed, LiFePO4 /graphene nanocomposites synthesized by stirring and dropping method obtains smaller potential difference, less charge transfer resistance and reduced polarization resulting from larger interplanar spacing, less Fe-Li anti-site defects and higher conductivity. The systematical study of charge transfer resistance, Li + diffusion coefficient, capacity and activation energy at 2.5 - 4.3 V from -30 - 50 °C indicates that compared with charge transfer process, lithium ion diffusion is the rate-determining step and that there is a transition from semi-infinite diffusion-controlled behavior to surface-controlled energy storage process as the temperature drops. The as-prepared sample acquires enhanced discharge capacity as high as 93.6 mAh g −1 (0.5 C) at -30 °C and better rate performance both. Simulation reveals that the lithium ion diffusion process is substantially impeded at low temperature resulting in uneven Li + distribution in the electrode. Graphical abstract: Image, graphical abstract